Anti-pulmonary fibrosis activity analysis of methyl rosmarinate obtained from Salvia castanea Diels f. tomentosa Stib. using a scalable process - Ma, Li; Liu, Chuntong; Zhao, Yuxiang; Liu, Mengke; Liu, Yunyi; Zhang, Huachang; Yang, Shude; An, Jing; Tian, Yuheng; Cao, Yinchuan; Qu, Guiwu; Song, Shuling; et al. (Frontiers in Pharmacology, 2024)
Pulmonary fibrosis is a progressive, irreversible, chronic interstitial lung disease associated with high morbidity and mortality rates. Current clinical drugs, while effective, do not reverse or cure pulmonary fibrosis and have major side effects，there are urgent needs to develop new anti-pulmonary fibrosis medicine, and corresponding industrially scalable process as well. Salvia castanea Diels f. tomentosa Stib., a unique herb in Nyingchi, Xizang, China, is a variant of Salvia castanea. and its main active ingredient is rosmarinic acid (RA), which can be used to prepare methyl rosmarinate (MR) with greater drug potential. This study presented an industrially scalable process for the preparation of MR, which includes steps such as polyamide resin chromatography, crystallization and esterification, using Salvia castanea Diels f. tomentosa Stib. as the starting material and the structure of the product was verified by NMR technology. The anti-pulmonary fibrosis effects of MR were further investigated in vivo and in vitro. Results showed that this process can easily obtain high-purity RA and MR, and MR attenuated bleomycin-induced pulmonary fibrosis in mice. In vitro, MR could effectively inhibit TGF-β1-induced proliferation and migration of mouse fibroblasts L929 cells, promote cell apoptosis, and decrease extracellular matrix accumulation thereby suppressing progressive pulmonary fibrosis. The anti-fibrosis effect of MR was stronger than that of the prodrug RA. Further study confirmed that MR could retard pulmonary fibrosis by down-regulating the phosphorylation of the TGF-β1/Smad and MAPK signaling pathways. These results suggest that MR has potential therapeutic implications for pulmonary fibrosis, and the establishment of this scalable preparation technology ensures the development of MR as a new antipulmonary fibrosis medicine.